(untitled) (Nóema, 2017)
The philosophical-juridical debate on the state of exception, between Carl Schmitt and Walter Benjamin, focuses on an anomaly that has often been related to language (by Benjamin himself, but also by Jacques Derrida and Giorgio Agamben). What link is there between language and anomy? A genealogy of the state of exception, if it must necessarily confront the threshold of language, must then also consider a further threshold (suggested by Schmitt): the threshold of writing. Without a focus on the conflict between orality (agraphos nomos) and literacy (written nomos), the genesis of the state of exception and its historical precedents would not be understood.